A Regime-Switching Approach to Studying Speculative Attacks : A Focus on European Monetary System Crises - Peria, Maria (The World Bank, 1999)
June 1999 - A regime-switching framework is used to study speculative attacks against European Monetary System currencies during 1979-93. Peria uses a regime-switching framework to study speculative attacks against European Monetary System (EMS) currencies during 1979-93. She identifies speculative attacks by modeling exchange rates, reserves, and interest rates as time series subject to discrete regime shifts. She assumes two states: tranquil and speculative. She models the probabilities of switching between states as a function of fundamentals and expectations. She concludes that: ° The switching models with time-varying transition probabilities capture most of the conventional episodes of speculative attacks. ° Speculative attacks do not always coincide with currency realignments. ° Both economic fundamentals and expectations determine the likelihood of switching from a period of tranquility to a speculative attack. The budget deficit appears to be an especially important factor driving the probability of switching to a speculative regime. Given the importance of anticipating and, wherever possible, avoiding crises, it might be useful to conduct forecasting exercises to determine whether the switching framework proposed here can be used to forecast crises in countries outside the sample. Because currency crises tend to occur simultaneously in two or more countries, it also might be useful to adapt the regime-switching framework to explore the role of contagion in explaining crises. This paper-a product of Finance, Development Research Group-is part of a larger effort in the group to understand currency crises. The author may be contacted at mmartinezperia@worldbank.org